Exercise-Induced Platelet Activation in Myocardial Infarction Survivors with Normal Coronary Arteriogram - Douste-Blazy, Ph; Sié, P; Boneu, B; Marco, J; Eche, N; Bernadet, P (Thrombosis and Haemostasis, 1984)
Platelet activation may participate in the pathophysiology of myocardial infarction occurring in patients with normal coronary arteriogram. We investigated this possibility in a series of 9 such patients (group A) during a standardized bicycle excercise test as myocardial infarction had occurred in all of them during or soon after strong physical exercise. Twelve patients with effort-induced angina and coronary atherosclerosis (group B) and eleven healthy subjects (group C) served as test groups. Peripheral venous blood was collected by separate venipuncture before, at peak exercise and during recovery. As a sensitive index of activation, the shape of the circulating platelets was examined with a phase contrast microscope after instantaneous fixation of the whole blood. The percentage of non strictly disc-shaped platelets with one or more thin pseudopods was determined. Simultaneously, the plasma levels of platelet factor 4 (PF4) and of beta-thromboglobulin (β-TG) were measured. At rest, there was no significant difference in the platelet morphology nor in the plasma levels of platelet specific proteins between the three groups. During exercise, a significant change in platelet shape occurred in group A and B patients and not in the healthy subjects. This platelet activation was not related to myocardial ischemia since it occurred to a similar extent in group B patients who developed electrocardiographic changes and in group A patients who did not. There was no detectable release of platelet proteins during exercise in any group.
Keywords: Platelet activation; Myocardial ischemia